Development of a Mobile Learning Application for Form 5 Mathematics with a Gamification Approach - TEOH, WEI TIAN; WAHID, NOORHANIZA (Applied Information Technology And Computer Science, 2024)
Mathematics is one of the compulsory subjects to be taken in Malaysia Certificate of Education (SPM). In 2020, some new topics including insurance and taxation were added-in the syllabus. These topics are causing difficulty to the students and feel more challenging to learn mathematics. Therefore, a mobile learning application named SPM Math Treasure with a gamification approach is developed to help Form 5 students improve their mathematics skills and increase students’ learning preferences in learning both insurance and taxation topics. SPM Math Treasure application has 3 modules including Lesson module, Tutorial module and Quiz module. Besides, Multimedia Mobile Content Development (MMCD) methodology is used to develop the SPM Math Treasure application. System Usability Scale (SUS) method is used to obtain the results of user acceptance test. It gets 80.75% positive feedback through this testing. In conclusion, Math Treasure is an application that is suitable for learning Mathematics.